2021
DOI: 10.1177/10598405211025771
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Perceived Supervisor Support and Workplace Bullying in School Nurses in Virginia

Abstract: Workplace bullying among school nurses is a significant problem with supervisors either contributing to or preventing such behavior. This study aimed to determine if support from nursing and school supervisors is associated with workplace bullying among Virginia school nurses. In this analysis of a cross-sectional survey, responses from 159 school nurses with two supervisors to the Survey of Perceived Supervisor Support and Short-Negative Acts Questionnaire were examined. Multiple linear regression analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This result is consistent with the literature [52,[58][59][60][61][62]. Recent studies, such as that by [63], confirm this negative link between hierarchical social support and workplace bullying. Employees who feel supported by their superiors may be more resilient to workplace bullying, while a lack of support can create an environment conducive to the proliferation of bullying behaviors, psychological distress, and the intention to leave the organization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the literature [52,[58][59][60][61][62]. Recent studies, such as that by [63], confirm this negative link between hierarchical social support and workplace bullying. Employees who feel supported by their superiors may be more resilient to workplace bullying, while a lack of support can create an environment conducive to the proliferation of bullying behaviors, psychological distress, and the intention to leave the organization.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between social support and workplace bullying has been firmly established in several studies [52,[58][59][60][61]. An empirical study conducted by [62] revealed a negative correlation between supervisor support and workplace bullying, a result confirmed by a recent study [63]. Employees who feel supported by their supervisors appear to be more resilient in the face of workplace bullying, while the lack of support can create an environment conducive to the proliferation of bullying behaviors.…”
Section: People Who Experience Workplace Bullying Are More Likely To ...mentioning
confidence: 82%
“…Amoo, Menlah, Garti, and Appiah (2021) pointed out that bullying in nursing is inadmissible, and shouldn't be tolerated by any person in such a profession. Thus, leadership support is significant in inhibiting workplace bullying (Sharma, Scafide, Maughan, & Dalal, 2021).…”
Section: Significance Of the Studymentioning
confidence: 99%